Zmart: Poverty Alleviation and Women Empowerment Program Through Micro Retail Shop Business - Randi Swandaru; Priyesta Rizkiningsih; Deden Kuswanda (Jurnal Reksa, 2022)
Zmart program is a micro retail shop empowerment program using zakat funds to alleviate poverty, especially in urban areas. This research examines the impact of Zmart program on poverty alleviation and women empowerment. The general poverty indicators based on poverty line and had kifayah standard show that the number of poverty decreases after Zmart intervention. In addition, the impact of Zmart also measured using BAZNAS Prosperity Index (BPI) with a score of 0.68, meaning Zmart has a good impact on its recipient. The Gender Development Index (GDI) in the Zmart program shows an increasing value from 75.97 to 139.32. It means that there is significant emancipation for the female group compared to the male group in the program. These results show that the Zmart program favorably empowers women as it is shown that the GDI value exceeds 100 points.